Faktor risiko yang mempengaruhi outcome pada pasien cedera kepala di RSUP Sanglah, Bali, Indonesia pada tahun 2018-2019 - I Gede Sutawan; Sri Maliawan; I Wayan Niryana (Intisari Sains Medis, 2021)
Background: Head injury or capitis trauma is a blunt/sharp force to the head or face resulting in temporary or persistent cerebral dysfunction. From a socio-economic point of view, the prognostic model by looking at baseline data on admission is an important factor in supporting cost-effective clinical decisions. This study aims to evaluate the risk factors that influence outcomes in head injury patients at Sanglah Hospital, Bali, Indonesia, in 2018-2019.Method: Prospective cohort study to see the effect of risk factors for head injury patients (exposure) with the outcome in the form of unfavorable conditions within 7 days. This research was conducted at the Surgery Department and Emergency Room Sanglah Hospital Denpasar- Bali for 6 months from September 2018-February 2019. Data were analyzed using SPSS version 16 for Windows.Results: Some of the factors significantly associated with and risk factors for the unfavorable outcome within 7 days in head injury patients who were treated at Sanglah General Hospital in 2018-2019 were hypotension, initial GCS 3-8, anisocoria pupil reflex, hypoxia, focal lesions, midline shift, and length of time operation ? 6 hours (p<0.05). Hypotensive blood pressure is the most dominant risk factor for the unfavorable outcome within 7 days of head injury patients admitted to Sanglah General Hospital (Adjusted OR: 5.4; 95% CI: 2.47-12.07; p=0.000).Conclusion: Hypotensive blood pressure is the most dominant risk factor for the unfavorable outcome within 7 days of head injury patients treated at Sanglah General Hospital in 2018-2019. Latar belakang: Cedera kepala atau trauma kapitis merupakan kekerasan tumpul/tajam pada kepala atau wajah yang berakibat disfungsi serebral sementara atau menetap. Dari sudut pandang sosioekonomi, model prognostik dengan melihat data awal saat masuk rumah sakit merupakan faktor penting dalam mendukung keputusan klinis yang cost-effective. Penelitian ini bertujuan untuk mengevaluasi faktor risiko yang mempengaruhi outcome pada pasien cedera kepala di RSUP Sanglah, Bali, Indonesia pada tahun 2018-2019Metode: Studi kohort prospektif untuk melihat pengaruh faktor resiko yang dimiliki pasien cedera kepala (exposure) dengan hasil luaran (outcome) berupa kondisi unfavourable dalam 7 hari. Penelitian ini dilakukan di Bagian Bedah FK UNUD/SMF Bedah Saraf RSUP Sanglah, Denpasar-Bali dan Instalasi Rawat Darurat RS Sanglah Denpasar-Bali selama 6 bulan dari bulan September 2018-Februari 2019. Data dianalisis menggunakan SPSS versi 16 untuk Windows.Hasil: Beberapa faktor yang berhubungan secara bermakna dan menjadi faktor risiko terjadinya outcome unfavorable dalam 7 hari pada pasien cedera kepala yang dirawat di RSUP Sanglah tahun 2018-2019 adalah hipotensi, GCS awal 3-8, reflek pupil anisokor, hipoksia, fokal lesi, midline shift, dan lama waktu tindakan operasi ? 6 jam (p<0,05). Tekanan darah hipotensi merupakan faktor risiko yang paling dominan terhadap outcome unfavorable dalam 7 hari pasien cedera kepala yang dirawat di RSUP Sanglah (Adjusted OR: 5,4; 95% IK: 2,47-12,07; p=0,000)Kesimpulan: Tekanan darah hipotensi merupakan faktor risiko yang paling dominan terhadap outcome unfavorable dalam 7 hari pasien cedera kepala yang dirawat di RSUP Sanglah tahun 2018-2019.